Institutional Monitoring: Evidence from the F‐Score. (17th July 2015) - Chung, Chune Young; Liu, Chang; Wang, Kainan; Zykaj, Blerina Bela
Abstract The extant literature shows that institutional investors engage in corporate governance to enhance a firm's long‐term value. Measuring firm performance using the F‐Score, we examine the persistent monitoring role of institutional investors and identify the financial aspects of a firm that institutional monitoring improves. We find strong evidence that long‐term institutions with large shareholdings consistently improve a firm's F‐Score and that such activity occurs primarily through the enhancement of the firm's operating efficiency. Other institutions reduce a firm's F‐Score. Moreover, we find evidence that, while monitoring institutions improve a firm's financial health, transient (followed by non‐transient) institutions trade on this information.